The Features Of Chess Teachers Training In Armenia - Kostanyan, Emma; Misakyan, Samvel; Gharakhanyan, Lusine (Զանգակ հրատ.)
In the article, we present the principles on which we conduct retraining, the specific features we consider when writing retraining programs, and teacher feedback. We have conducted research with teachers, the results of which have shown what factors, according to the teachers, enhance the effectiveness of teaching younger students as a result of retraining. Our research allows us to design the retraining program more effectively. The research results clarify which teaching methods teachers use that are more effective. Our research goal is to identify effective teaching methods that contribute to developing younger students' chess skills. During the research, we discovered that applying teaching methods during group work helps teachers implement these methods and identify challenges specifically in the context of group activities. Meanwhile, the instructor can provide feedback during training.
Keywords: Education